GAMBARAN HISTOPATOLOGI PARU PADA PASIEN COVID-19: SEBUAH TINJAUAN LITERATUR - Hermafasya, Ayu Octarin; Asri, Aswiyanti; Hardisman, Hardisman; Yenita, Yenita; Anggrainy, Fenty; Yulistini, Yulistini (SINERGI : Jurnal Riset Ilmiah, 2025)
COVID-19 was declared a pandemic on March 11, 2020, posing a global challenge for healthcare workers. Understanding the histopathological characteristics of the lungs in COVID-19 patients is crucial for elucidating the disease's pathophysiology. This literature review analyzes pulmonary histopathological findings based on 34 articles retrieved from PubMed, including case reports, case series, and other descriptive studies published between March 2020 and April 2022. A total of 264 patients were examined, the majority of whom were male (184 individuals) with an average age of 64 years. Most patients had comorbidities such as hypertension, cardiovascular disease, diabetes, obesity, and chronic pulmonary disease. Key histopathological findings included hyaline membrane formation, endothelial cell damage, interstitial cell involvement, alveolar and interstitial edema, hemorrhage, microthrombi, and fibrin deposits. These histological patterns suggest diffuse alveolar damage (DAD) in both exudative and proliferative phases, organizing pneumonia (OP), and acute fibrinous organizing pneumonia (AFOP), with varying combinations observed in individual patients.